Is Salivary S100B a Biomarker of Traumatic Brain Injury? A Pilot Study - Janigro, Damir; Kawata, Keisuke; Silverman, Erika; Marchi, Nicola; Diaz-Arrastia, Ramon (Frontiers in Neurology, 2020)
Traumatic brain injury (TBI) results in short and long-term disability neurodegeneration. Mild traumatic brain injury (mTBI) represents up to 85% of head injuries; diagnosis and early management is based on computed tomography (CT) or in-hospital observation, which are time- and cost- intensive. CT involves exposure to potentially harmful ionizing radiation and >90% of the scans are negative. Blood-brain barrier (BBB) damage is suspected pathological event post-TBI contributing to long-term sequelae and a reliable and rapid point-of-care test to screen those who can safely forego acute head CT would be of great help in evaluating patients with an acute mTBI. In this pilot study, 15 adult patients with suspected TBI (mean age = 47 years, range 18–79) and 15 control subjects (mean age = 33 years, range 23–53) were enrolled. We found that the average salivary S100B level was 3.9 fold higher than blood S100B, regardless of the presence of pathology. [S100B]saliva positively correlated with [S100B]serum (Pearson' coefficient = 0.79; p < 0.01). Salivary S100B levels were as effective in differentiating TBI patients from control subjects as serum levels (Control vs. TBI: p < 0.01; Serum ROCAUC = 0.94 and Saliva ROCAUC = 0.75). I These initial results suggest that measuring salivary S100B could represent an alternative to serum S100B in the diagnosis of TBI. Larger and confirmatory trials are needed to define salivary biomarker kinetics in relation to TBI severity and the possible roles of gender, ethnicity and age in influencing salivary S100B levels.